THE EFFECT OF STUDENTS’ ACHIEVEMENT IN STUDYING VOCABULARY THROUGH SCRAMBLE METHOD AT SMP N 1 KUALUH HULU - Ismi Yulizar (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2020)
The Aim of this research is to know whether any significant effect of studyingvocabulary through scramble method. Thisresearch is an experimentalresearch. Thepopulation of this research was the eighth grade students of SMP N 1 Kualuh huluin academic year 2018/2019. The total number of the population was 276 students.In this case 78 students were taken as the samples. These samples were dividedinto two groups. The first group was an experimental group which was taught byusing Scramble Method and the second group was control group which was taughtwithout using Scramble method or using conventional technique. This research usedthe quantitative data. The quantitative data were analyzed by using test of wordscramble was consisted of 5 items, filling letters in box was consisted of 5 itemsand guessing the picture was consisted 10 items. The calculation of the reliabilityof the test shows that the reliability is sufficient (0,5). The data were analyzed byusing t-test. The result of calculating the t-test shows that tobserved is higher than ttable8,18 > 1,66 (p = 0,05) with df 76. tobserved> tvalue> ttable. 8,18 > 2,36 > 1,66. It couldbe concluded that Ha is accepted. It means that there is significant effect of scramblemethod on Students’ Achievement in Studying Vocabulary.